( x 3 + 3 x 2 + 3 x + 2 ) P ( x − 1 ) = ( x 3 − 3 x 2 + 3 x − 2 ) P ( x )
Let P ( x ) be a polynomial with real coefficients such that it satisfies the above equation ∀ x ∈ R , where P ( 2 ) = 8 4 . Submit the value of P ( 1 0 ) as your answer.
Bonus - Generalize P ( x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nailed it! Fantastic!
Same method!
This is a very elegant solution! Of course, better than mine!
Ingenious! This might be a stupid question, but does the 7 come from 82?
awesome man, same thing i did
In what follows, we are going to use the following notation w 1 = e 3 π i and w 2 = e 3 2 π i . Now it is not difficult to see that the given equation can be written in the following way ( x + 2 ) ( x − w 2 ) ( x − w 2 ) P ( x − 1 ) = ( x − 2 ) ( x − w 1 ) ( x − w 1 ) P ( x ) Therefore the numbers − 2 , w 2 , w 2 are roots of P ( x ) , and the numbers 2 , w 1 , w 1 are roots of P ( x − 1 ) . Using that if a number α is a root of a polynomial P ( x − 1 ) , then α − 1 is a root of P ( x ) , we obtain three other roots of P ( x ) by subtracting 1 from each number 2 , w 1 , or w 1 , respectively. Those roots will be 1 , w 1 − 1 = w 2 , w 1 − 1 = w 2 , but only 1 is a new root because we already know that w 2 and w 2 were roots of P ( x ) . So a partial conclusion here would be that P ( x ) has the roots 1 , − 2 , w 2 , w 2 . Then P ( x ) = ( x − 1 ) ( x + 2 ) ( x − w 2 ) ( x − w 2 ) Q ( x ) where Q ( x ) is a polynomial.
By substituting P ( x ) by the latter expression in the given equation of the problem and cancelling the factors that appear in both sides, we obtain the equation ( x + 1 ) Q ( x − 1 ) = ( x − 1 ) Q ( x ) ( ∗ ) .
From this equations and using a reasoning similar to the one that we used before, we obtain that Q ( x ) has the roots − 1 and 0 and therefore can be written like Q ( x ) = x ( x + 1 ) R ( x ) where R ( x ) is a polynomial. By substituting in ( ∗ ) and simplifying again, we get R ( x − 1 ) = R ( x ) . The latter equation implies that R ( x ) = R ( x + n ) for any integer n , and this implies that R ( x ) is a constant polynomial. Denoting this constant by c we obtain that P ( x ) = c x ( x + 1 ) ( x − 1 ) ( x + 2 ) ( x − w 2 ) ( x − w 2 ) . Using the condition P ( 2 ) = 8 4 we get that c = 2 1 , and therefore P ( 1 0 ) = ( 1 / 2 ) ( 1 0 ) ( 1 1 ) ( 9 ) ( 1 2 ) ( 1 0 2 + 1 0 + 1 ) = 6 5 9 3 4 0 .
+1 Remarkable observation on roots of P ( x ) and P ( x − 1 )
Problem Loading...
Note Loading...
Set Loading...
Given: ( x 3 + 3 x 2 + 3 x + 2 ) P ( x − 1 ) = ( x 3 − 3 x 2 + 3 x − 2 ) P ( x )
⟹ ( x + 2 ) ( x 2 + x + 1 ) P ( x − 1 ) = ( x − 2 ) ( x 2 − x + 1 ) P ( x )
⟹ P ( x − 1 ) P ( x ) = ( x − 2 ) ( x 2 − x + 1 ) ( x + 2 ) ( x 2 + x + 1 )
⟹ x = 3 ∏ n P ( x − 1 ) P ( x ) = x = 3 ∏ n ( x − 2 ) ( x 2 − x + 1 ) ( x + 2 ) ( x 2 + x + 1 )
⟹ x = 3 ∏ n P ( x − 1 ) P ( x ) = x = 3 ∏ n ( x − 2 ) ⋅ T x − 1 ( x + 2 ) ⋅ T x ( ∗ )
where T x = x 2 + x + 1
Clearly, ( ∗ ) is a telescoping product, evaluating it, we have,
P ( 2 ) P ( n ) = 4 ! 1 7 ( n − 2 ) ! ( n + 2 ) ! ( n 2 + n + 1 )
⟹ P ( n ) = 2 n ( n + 2 ) ( n 2 − 1 ) ( n 2 + n + 1 )
∴ P ( 1 0 ) = 6 5 9 3 4 0